Effect of neoadjuvant chemoradiation in rectal cancer lymph node staging and survival: a systematic review and meta-analysis - Armas-Maldonado, Cristina Alejandra (2022)
Objectives: To assess the efficacy of surgical resection of more than 12 lymph nodes versus fewer than 12 lymph nodes in patients with rectal cancer after neoadjuvant treatment with chemoradiation. Materials and Methods: We conducted a search in Pubmed, Scopus, Web of Science, EMBASE, selecting randomized clinical trials and prospective cohort studies that compared the number of LNs in rectal cancer resected after neoadjuvant treatment. Two independent researchers reviewed and selected the studies that underwent the risk of bias assessment using the NOS tool, finally, the random effects model and the inverse variance method were executed. Results: A total of 3964 articles were reviewed, of which 10 articles were included in the systematic review. The study showed that a lymph node harvest of less than 12 nodes (NL<12) is not related to lower overall survival compared to a finding of more than 12 nodes (NL>12) (HR 0.75; CI 95% 0.52-1.07; p=0.09 ; I2=63%) nor in disease-free survival (HR 0.69; 95% CI 0.36-1.33; p=0.21; I2=92%;). Regarding recurrence (RR 1.46; 95% CI 0.80-2.68; p=0.11; I2=1%;) no relationship was found when comparing both groups either. Conclusions: The present systematic review showed that there is no relationship between a finding of less than 12 lymph nodes in a lower overall survival nor to a lower disease-free survival when compared with a finding of more than 12 nodes.